Immigrants in the Labour Market in Poland - Kisiel, Roman; Mozol, Magda; Maciejewska, Aneta (Olsztyn Economic Journal, 2015)
Labour immigrants play an increasingly important role in balancing the situation on labour market in Poland. Given the low demographic growth rate, pessimistic forecasts, mass labour emigration and structural maladjustment of the labour market, Poland faces the huge challenge of preventing a collapse of the pension system and public finance. A solution to the problem could be, for example, an inflow of foreign workers. The character of this paper is both theoretical and practical. The purpose of the article is to analyse the phenomenon of labour immigration in Poland (legal regulations governing employment of foreign workers, scale of immigration) and to present the opinions of employers concerning the employment of foreigners and the obstacles associated with it. The results of surveys conducted among employers in Warmian-Masurian voivodeship will be used for this purpose. According to the respondents, the main advantages of employing immigrants are lower costs (28%) and filling the gaps in the labour market (21%), whereas the biggest obstacle concerns complicated legal regulations (29%).